Detection of Partial Discharge in Oil Filled-Tank using Acoustic in Audio Frequency - Mochammad Wahyudi; Noor Akhmad Setiawan; Bambang Sugiyantoro; I Made Yulistya Negara; Gilang Adityasakti (Department of Electrical Engineering ITS and FORTEI, 2021)
In this paper, the acoustic signal within an audio sonic range emitted by partial discharge (PD) in an oil-filled cylindrical tank was investigated. The PD was generated by point-to-flat electrodes subjected to a high-voltage DC. The PD source location, installation method, and sensor microphone, as well as the electrode gap distance, were varied. Subsequently, acoustic waveforms and their frequency spectrum, as well as the PD current, were analyzed. The results showed that transient acoustic signals indicated the emergence of PD. The acoustic sensor attached to the outer wall of the tank (contact type) was more sensitive than the sensor that had a distance from the tank (non-contact type). Sensor contact type acoustic signals placed parallel to the location of the PD source provided a more accurate signal form compared to those set nonparallel to the frequency spectrum, which was relatively flat. A closer electrode distance caused the duration, acoustic signal amplitude as well as the currents to be more considerable. For the identical variable, the acoustic signal form was not related to the current signal despite the same signal duration. Besides, locations of sources of the PD notably influenced the signal form, but it did not apply for the current signal.Keywords: acoustic, audio frequency, fast Fourier transform, high-frequency current transformer, oil transformer, partial discharge